ANALISIS PENYEBAB KONSUMEN BERBELANJA DI PASAR TRADISIONAL (STUDI KASUS DI PASAR TRADISIONAL SUNTER KIRANA) - Surej Dhillon; Lelly Christin (Business Management Journal, 2017)
Nowadays, traditional market can still survive among modern market. Due to that reason, the researcher is interested in analyzing the factor why consumer still want to shop at traditional market. The subject of the research is Sunter Kirana Market. For the data collection, the researcher is using interview to 100 respondents with descriptive analysis.  From the research is known that the price factor, product, location and consumer behaviour are the reasons why consumer still want to shop at traditional market. Key Words,Consumer, Traditional Market